Formaldehyde Pollution in Ahvaz, Iran: Spatiotemporal Trends and Health Risks - Faezeh Borhani; Mohammad Hashemzadeh; Samira Andam; Seyed Mohsen Mousavi (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
We present a satellite-driven, four-year assessment of formaldehyde (HCHO) over Ahvaz that quantifies its spatiotemporal variability, meteorological controls, and health risk. Using Sentinel-5P/TROPOMI (2019–2022) together with MERRA-2/GLDAS/AIRS fields, we relate HCHO to co-pollutants (CO, NO₂, SO₂) and meteorology (precipitation, temperature, wind speed, relative humidity, dew point) and map hotspots via IDW; health risks are evaluated with RAIS. HCHO correlates positively with temperature (r = 0.92) and negatively with relative humidity (r = -0.84) and precipitation (r = -0.65); the wind-speed link is moderately positive (r = 0.46), with primary co-pollutants are weak (CO: r ≈ 0.08; NO₂: r ≈ -0.02). Interannually, 2020 shows the highest HCHO and 2021 the lowest (annual mean ≈8% lower in 2021), with persistent hotspots along the southeastern industrial corridor. IUR-based lifetime inhalation cancer risk peaks in 2020 at 506 expected excess cases citywide and is lowest in 2021 at 468. These quantitative results highlight temperature-driven photochemistry and moisture-related removal as key controls on HCHO and motivate strengthened air-quality management to mitigate exposure and protect public health in Ahvaz.